Preparation and characterizations of activated carbon from kenaf fiber for equilibrium adsorption studies of copper from wastewater - Chowdhury, Z.Z.; Islam, M.S.; Khan, R.A.; Zain, Sharifuddin Md (2012)
The potential of activated carbon prepared from kenaf fiber (KF) to remove copper (II) from aqueous effluents was investigated. The fibers were first semi-carbonized, then impregnated with potassium hydroxide (KOH) and finally activated by using carbon dioxide (CO 2) gas to produce activated carbon. Pore structure and physical characteristics of the prepared kenaf fiber activated carbon (KFAC) were determined. Adsorption studies for divalent copper (Cu) ions were carried out to delineate the effect of contact time, temperature, pH and initial metal ion concentration on equilibrium adsorption capacity. The experimental data followed pseudo-second-order kinetics and Elovich Model than pseudo-first-order. Langmuir, Freundlich and Temkin models were implemented to analyze the parameters for adsorption at 30 °C, 50 °C and 70 °C. Thermodynamic parameters such as ΔG o, ΔH o and ΔS o which represent Gibbs free energy, enthalpy and entropy, respectively, were evaluated. It was concluded that activated carbon from kenaf fiber (KFAC) can be used as an efficient adsorbent for removal of Cu (II) from synthetic wastewater. © 2012 Korean Institute of Chemical Engineers, Seoul, Korea.